2022
DOI: 10.3389/fnins.2022.953356
|View full text |Cite
|
Sign up to set email alerts
|

Reconfiguration of static and dynamic thalamo-cortical network functional connectivity of epileptic children with generalized tonic-clonic seizures

Abstract: ObjectiveA number of studies in adults and children with generalized tonic-clonic seizure (GTCS) have reported the alterations in morphometry, functional activity, and functional connectivity (FC) in the thalamus. However, the neural mechanisms underlying the alterations in the thalamus of patients with GTCS are not well understood, particularly in children. The aim of the current study was to explore the temporal properties of functional pathways connecting thalamus in children with GTCS.MethodsHere, we recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 63 publications
2
4
0
Order By: Relevance
“…The present findings demonstrated that inter-network dFC between subnetworks in children with GTCS showed a significant increase in State 2 and a decrease in State 1 as compared to the control group. Such direction of change are consistent with previous findings that children with GTCS showed both an increase and decrease in dFC strength of some specific networks ( Li et al, 2022a , c ). However, previous studies on adults with GTCS only detected increased FC variabilities between the DMN and cognition-related networks ( Jia et al, 2020 ; Yang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present findings demonstrated that inter-network dFC between subnetworks in children with GTCS showed a significant increase in State 2 and a decrease in State 1 as compared to the control group. Such direction of change are consistent with previous findings that children with GTCS showed both an increase and decrease in dFC strength of some specific networks ( Li et al, 2022a , c ). However, previous studies on adults with GTCS only detected increased FC variabilities between the DMN and cognition-related networks ( Jia et al, 2020 ; Yang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…FC variability between the DMN and cognition-related networks showed a significant increase. In our previous studies, we applied the dFC method in children with GTCS to explore FC characteristics of specific networks ( Li et al, 2022a , c ). Children with GTCS showed both an increase and decrease in dFC within the DMN and the thalamocortical network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we found that patients failed to flexibly change the network reorganization across resting and motor states, which might be related to the hyper‐integration of brain networks caused by disease. 54 At the same time, we also discovered the instability of the patient's functional activity across states, which was found to be contrary to changes observed in spatial profiles of brain network. Distributed decreased across‐state connectivity in patients with GTCS also suggested the instability of the epileptic brain induced by motor tasks.…”
Section: Discussionmentioning
confidence: 69%
“…Frontotemporal regions are involved in the majority of patients with generalized epilepsy, 52,53 which might lead to a fixed and over‐integrated network architecture in epilepsy. Here, we found that patients failed to flexibly change the network reorganization across resting and motor states, which might be related to the hyper‐integration of brain networks caused by disease 54 . At the same time, we also discovered the instability of the patient's functional activity across states, which was found to be contrary to changes observed in spatial profiles of brain network.…”
Section: Discussionmentioning
confidence: 73%